Understanding the value of plant diversity for ecosystem functioning through niche theory - Turnbull, L; Isbell, F; Purves, D; Loreau, M; Hector, A (Royal Society, 2016)
Biodiversity experiments have generated robust empirical results supporting the hypothesis that ecosystems function better when they contain more species. Given that ecosystems provide services that are valued by humans this inevitably suggests that the loss of species from natural ecosystems could diminish their value. This raises two important questions. First, will experimental results translate into the real world, where species are being lost at an alarming rate? And second, what are the benefits and pitfalls of such valuation exercises? We argue that the empirical results obtained in experiments are entirely consistent with well-established theories of species coexistence. We then examine the current body of work through the lens of niche theory and highlight where closer links with theory could open up opportunities for future research. We argue that niche theory predicts that diversity-functioning relationships are likely to be stronger (and require more species) in the field than in simplified experimental settings. However, we caution that while many of the biological processes that promote coexistence can also generate diversity-function relationships there is no simple mapping between the two. This implies that valuation exercises need to proceed with care.